2013
DOI: 10.1101/lm.030171.112
|View full text |Cite
|
Sign up to set email alerts
|

Visual object pattern separation varies in older adults

Abstract: Young and nondemented older adults completed a visual object continuous recognition memory task in which some stimuli (lures) were similar but not identical to previously presented objects. The lures were hypothesized to result in increased interference and increased pattern separation demand. To examine variability in object pattern separation deficits, older adults were divided into impaired and unimpaired groups based on performance on a standardized serial list-learning task. Impaired older adults showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 54 publications
17
56
1
Order By: Relevance
“…First, a majority of aged rats were impaired on spatial discriminations in which the distance between target and foil locations was ,88 cm. These data support an emerging consensus in the field of cognitive aging that age-associated discrimination deficits in humans and animal models are observed when the test stimuli are similar or share common features (Stark et al 2010(Stark et al , 2013Burke et al 2011;Yassa et al 2011a,b;Ryan et al 2012;Holden et al 2013;Reagh et al 2014Reagh et al , 2016. Moreover, the observation that a subset of aged rats were Figure 5.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…First, a majority of aged rats were impaired on spatial discriminations in which the distance between target and foil locations was ,88 cm. These data support an emerging consensus in the field of cognitive aging that age-associated discrimination deficits in humans and animal models are observed when the test stimuli are similar or share common features (Stark et al 2010(Stark et al , 2013Burke et al 2011;Yassa et al 2011a,b;Ryan et al 2012;Holden et al 2013;Reagh et al 2014Reagh et al , 2016. Moreover, the observation that a subset of aged rats were Figure 5.…”
Section: Discussionsupporting
confidence: 82%
“…In support of this interpretation, discrimination abilities are impaired in healthy aged humans (Toner et al 2009;Stark et al 2010Stark et al , 2013Holden et al 2012Holden et al , 2013Ryan et al 2012;Reagh et al 2014Reagh et al , 2016, monkeys (Burke et al 2011), and rats (Burke et al 2010(Burke et al , 2011). An intriguing aspect of these deficits is that older adults who do not show episodic memory loss can be impaired relative to young adults at difficult discriminations between similar stimuli, but not easy discriminations between unique stimuli (Stark et al 2013;Reagh et al 2014Reagh et al , 2016.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…First, patients and healthy controls were tightly matched on age because it has been demonstrated that pattern separation performance is negatively correlated with age (Holden, Toner, Pirogovsky, Kirwan, & Gilbert, 2013;Stark, Yassa, Lacy, & Stark, 2013). Second, patients and controls performed equally in the CSCT, excluding encoding deficit due to impaired attention or slowing of information processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing body of evidence suggests that older adults exhibit a deficit in encoding new memories so that they are distinct from previously stored items. In other words, they show impaired pattern separation (Carr, Castel & Knowlton, 2015;Holden, Toner, Pirogovsky, Kirwan & Gilbert, 2013). For example, recent research suggests that visual recognition impairments in older adults are due to an impaired ability to identify stimulus novelty (Yassa & Stark, 2008).…”
Section: Time Manages Interference 3 Time Manages Interference In Vismentioning
confidence: 99%